Improved Exposure To Blue Light For Bacterial Death Of Staph - Endah Robbiyati (Universitas Airlangga, 2019)
ABSTRACTIn this study, bacteria Gram-positive Staphylococcus aureus is exposed to a blue LED light source (light-emitting diode) to determine the appropriate energy to kill the exposure-caused bacteria. The longest exposure times are 1200, 1800, 2400, 3000 seconds, and power 28.098, 56.561, 74.882, and 96.369 MW. The number of bacterial colonies incubated by TPC (total plate number) at 37 degrees 24-48 hours while the plant is alive. Determine the correct energy caused by exposure to the blue LED lamp, therefore, perform mold analysis, non-compliance, and quantitative energy analysis. These results show that the death of streptococcus skin is generally affected by high energy. From this study, we found that 74,882 MW of energy and 179,716.8 MJ of bacteria per 2,400 seconds were the best energy week.Keywords: Staphylococcus epidermidis, a blue LED, exposure time, the power of exposure, CFU